Напрями попередження наукового плагіату - Ульянова, Галина Олексіївна; Ульянова, Галина Алексеевна; Ul'janova, Galina (My University, 2013)
The article is devoted the scientific plagiarism. Scientific plagiarism consists in appropriation of authorship to the result of scientific activity, which is the object of the intellectual property rights. The negative consequences of scientific plagiarism and the basic directions of its warning are determined.
Ульянова Г. О. Напрями попередження наукового плагіату / Г. О. Ульянова // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 420-428.
Keywords: плагіат; науковий плагіат; привласнення авторства; наукова діяльність; попередження наукового плагіату; плагиат; научный плагиат; присвоение авторства; научная деятельность; предупреждение научного плагиата; plagiarism; scientific plagiarism; appropriation of authorship; scientific activity; warning scientific plagiarism